Keterampilan Sulam Tumpar Khas Suku Daya Benuaq Bagi Siswa Sekolah Dasar - Siska Oktaviani; Ratna Khairunnisa; Annisa Qomariah (CV. Multi Kreasi Media, 2025)
The purpose of this community service activity was to enhance participants’ understanding of embroidery techniques and to develop elementary school students’ skills in producing embroidered products, particularly those applying the sulam tumpar technique. The activity was implemented using a workshop method that consisted of two main components, namely the delivery of material on embroidery techniques and hands-on practice in creating embroidered products. The implementation process involved several stages, including coordination with the partner institution, SDN 004 Samarinda Utara, preparation of the necessary tools and materials, and the execution of the workshop. The participants were fourth-grade students of SDN 004 Samarinda Utara. The sulam tumpar creative training was carried out as planned, as evidenced by the high level of student enthusiasm throughout the activity from beginning to end during the process of making sulam tumpar wall decorations. Furthermore, the activity received positive responses from the school community, including the principal and teachers.